PROFIL PERILAKU SEKS SEBELUM MENIKAH PADA SISWA SEKOLAH MENENGAH PERTAMA (SMP) DI KABUPATEN BANYUMAS - Rr. Setyawati; Suwarti Suwarti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2011)
The purpose of this study was to determine the profile of sexual behavior in junior high school students Banyumas. This research uses an explanatory survey research, with a cross sectional study including three school study. Lokasi namely SMPN 2 Karanglewas, SMPN 3 Purwokerto and SMP Gunung Jati. Data collection method to use: the questionnaire, which is to expose junior high students and Sexual Behavior Interview with the technique of open questions to find out the factors that encourage sexual behavior. Data analysis was performed by quantitative descriptive analysis with the percentages and cross tabulation. From the above results it can be concluded that sexual behavior before marriage in junior high school students covering all the indicators on the questionnaire that has been dating research. Responden as much as 50 percent with sexual behaviors that occur include the most widely seen movie porn as much as 53 percent, 60 percent of the source acquire porn magazines and porn films derived from friends. Other sexual behaviors include masturbation / masturbation as much as 52 percent, 50 percent of kissing lips, kissing her neck chest 23 percent to sexual relations. The influence of peers is very large for adolescents, it is based on data that 70 percent of teens get pornographic magazines from friends, 61 percent saw a porn film obtained from peers as well. The period of 0-6 months is the shortest time for teens to 70 percent of kissing lips, neck chest as much as 88 percent. It means that teenagers do not take a long time to kiss up to the sexual area around the neck and chest. Sexual intercourse has been the respondent as much as 3 people. Keywords: Sexual Behavior of Teenager